Patterns of brain metastasis in anaplastic lymphoma kinase - rearranged and epidermal growth factor receptor-mutated lung cancer patients in magnetic resonance imaging - Batra, Ullas; Mahawar, Vivek; Jajodia, Ankush; Razdan, Avinash; Mahanthi, Himanshu; Koyyala Babu, Venkata Pradeep (South Asian Journal of Cancer, 2019)
Introduction: The optimal management of neuroparenchymal lesions in cases of lung cancer is exigent as this frequent yet notorious complication negatively impacts the morbidity and mortality index. Aims: This study is aimed at recognizing various patterns of neuroparenchymal metastasis in patients of lung cancer with epidermal growth factor receptor (EGFR)- and anaplastic lymphoma kinase (ALK)-positive mutations. Material and Methods: The radiological findings of the neuroparenchymal lesions were analyzed and the statistical data were charted. We identified two groups of patients with neuroparenchymal lesions among a cohort of 340 patients having EGFR-positive (68) and ALK-positive (24) mutations (total: 24 + 68 = 92). Results: We observed that among the ALK group, leptomeningeal spread was less compared to EGFR group (2/24 as opposed to 18/68). Morphological heterogeneity and central necrosis in the parenchymal lesion which were associated with unfavorable outcomes were predominant in ALK group (8/24) as opposed to EGFR group (2/68). Ancillary findings but pertinent to survival and morbidity such as presence of perilesional edema, hemorrhage, and hydrocephalus on magnetic resonance imaging were also analyzed. The mutation-specific differential imaging spectrum could be attributed to biological differences between these cancers.
Keywords: Anaplastic lymphoma kinase mutation; epidermal growth factor receptor; lung cancer; magnetic resonance patterns; neuroparenchymal